English grammar in context: selected material for students in the eighth year of basic education at fray Vicente Solano high school - Campoverde Campoverde, Martha Yolanda
on which this study is based give a clear understanding of how learning grammar in context helps learners improve English grammar. This study also considers some theories related to the development of strategies and techniques to improve the teaching-learning grammar process. The instruments of the This research study focuses on the development of activities to teach grammar in context to students of Eighth Year of Basic Education at Fray Vicente Solano High School. The theories research study are questionnaires, a pre-test, and a post-test. After finishing the application of grammar activities in context, the results obtained from this research prove that learners do learn grammar better when it is presented in context, not in isolation. Therefore, grammar activities based on meaningful contexts give learners the opportunity to improve the learning of grammar and also lead them to authentic interaction inside and outside the classroom setting.